Who is Poorer? Poverty by Age in the Developing World - Evans, Brooks (World Bank E-Library Archive, 2015)
This note shows that based on headcount poverty rates, at the household level, households with elderly members are roughly equally poor to non-elderly households, though with variation when using more detailed compositions, and the elderly are less poor than children in 98 percent of the countries sampled when comparing different age groups. Further, as a share of the poor, elderly average only 10 percent, children 36 percent, and adults 54 percent. Moderate equivalence adjustments result in a four percentage point change in the number of countries with children better off than elderly. (A separate note provides detailed sensitivity analysis). These results can be seen as a starting point for further analysis that would look at the reasons behind differences between countries as well as age sub-groups within countries. The findings provide preliminary evidence that households with elderly, and especially elderly individuals are often not the most poor. The analysis is relevant to countries considering new policies or reforms of existing programs targeting particular age groups, such as the elderly or children